ISOLASI DAN KARAKTERISASI SENYAWA TURUNAN ACETOGENIN DARI DAUN SIRSAK (Annona muricata) SERTA UJI TOKSISITAS - Pradana, Pulung Yudhariska; Suratmo, Suratmo; Retnowati, Rurini (Jurnal Ilmu Kimia Universitas Brawijaya, 2015)
The research is aims to determine acetogenin derivative isolated from graviola leaf (Annona muricata) and study their toxicity activity. Graviola leaf powder was macerated using ethanol and its isolate were fractionated using methanol. Characterization acetogenin compound in methanol fraction using kedde test, UV-Vis and FTIR spectrophotometer. Kedde test result showed the presence of colour changing of dot to pink. UV-Vis data shows that absorption at 222 nm. FTIR spectra data showed the presence of cluster of C=O, C-C(=O)-O and O-C-C with the peak of the wave number at 1741 cm-1 , 1164 cm-1 and 1076 cm-1. The identification result showed that methanol fraction is acetogenin. The results of toxicity tests methanol fraction from the leaves of the soursop has LC50 value of 35.51 ppm.